Is the concentration of C-reactive protein in bacteraemia associated with age? - Blaasaas Karl G; Wester Astrid L; Wyller Torgeir (Immunity & Ageing, 2008)
Abstract Background C-reactive protein (CRP) is an indicator of inflammation, and is often used in the diagnosis of bacterial infections. It is poorly known whether CRP in bacterial infection is age-dependent. Methods Adult patients with a positive blood culture with E. coli or S. pneumoniae during 1994–2004 were included. CRP measured on the same date as the blood cultures were drawn (CRP1), 2–3 days (CRP2) and 4–7 days later (CRP3), were retrieved. The patients were divided into three age groups, < 65, 65–84, and ≥ 85, respectively. We studied three cut-off values for CRP and produced age-specific receiver operating characteristics (ROC) curves, using patients with acute coronary or cerebral infarction as controls. Results 890 patients and 421 controls were available. There was a statistically significant negative correlation between age and CRP1 – 0.072 (p = 0.032). The median CRP1 and CRP2 were significantly higher in the youngest age group. The area under the ROC-curve for the youngest age group was significantly greater than that of the two other age groups, but we found no statistically significant differences in sensitivity related to age. The diagnostic sensitivity of CRP was better for S. pneumoniae than for E. coli, 92.6% vs. 88.0% (p = 0.046) for a cut-off value of 40 mg/L, and 82.4% vs. 61.5% (p =< 0.01) for a cut-off value of 120 mg/L. Conclusion CRP is better in identifying infection with S. pneumoniae than with E. coli. We found a weakening of the CRP-response with age, but this is hardly of clinical significance.